Self-folding origami: shape memory composites activated by uniform heating - Tolley, Michael T; Felton, Samuel M; Miyashita, Shuhei; Aukes, Daniel; Rus, Daniela; Wood, Robert J (Smart materials and structures, 2014)
Self-folding is an approach used frequently in nature for the efficient fabrication of structures, but is seldom used in engineered systems. Here, self-folding origami are presented, which consist of shape memory composites that are activated with uniform heating in an oven. These composites are rapidly fabricated using inexpensive materials and tools. The folding mechanism based on the in-plane contraction of a sheet of shape memory polymer is modeled, and parameters for the design of composites that self-fold into target shapes are characterized. Four self-folding shapes are demonstrated: a cube, an icosahedron, a flower, and a Miura pattern; each of which is activated in an oven in less than 4 min. Self-sealing is also investigated using hot melt adhesive, and the resulting structures are found to bear up to twice the load of unsealed structures.